2022
DOI: 10.1002/wsb.1335
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the precision of wild boar density estimations

Abstract: Effective management of wild boar (Sus scrofa) populations has to be based on precise estimates of local densities. The development of an effective and cost-efficient technique to cope with this need has always represented a challenge for wildlife managers and researchers. Drive counts, hunting bags, and Random Encounter Model (REM) are among the most frequently used techniques, with the latter recently gaining wide recognition. We sought to compare the 3 methods in terms of their suitability for management, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Recent studies have shown that current methods used to estimate population abundance of game species need to be improved to be more useful for management purposes ( Guerrasio et al, 2022 ), particularly as hunted ungulates have reached unprecedented high densities in most of Europe ( Apollonio, Andersen & Putman, 2010 ) leading to increasing human-wildlife conflicts ( e.g. , Massei, Roy & Bunting, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that current methods used to estimate population abundance of game species need to be improved to be more useful for management purposes ( Guerrasio et al, 2022 ), particularly as hunted ungulates have reached unprecedented high densities in most of Europe ( Apollonio, Andersen & Putman, 2010 ) leading to increasing human-wildlife conflicts ( e.g. , Massei, Roy & Bunting, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Effective wild boar management and population monitoring have relied on accurate estimative of population density and spreading [ 103 ], with wild boar presence in Brazil confirmed since the 1980's [ 9 ]. Despite few studies of individual numbers and behavior in Brazil, higher female and piglet population in different conservation units have revealed ideal nursery habitats for wild boars, particularly due to hunting prohibition in such areas [ 17 ].…”
Section: Population Monitoring Disease Surveillance and Future Researchmentioning
confidence: 99%
“…In the last few decades, wild boar populations underwent a considerable expansion that led to the colonisation of new habitats such as agricultural lands and peri-urban and urban areas. The Italian Apennines showed a high wild boar population, ranging from four to eighteen animals for Km 2 [25]. A more recent study on wild boar distribution from Western Europe to Central-Northern Asia showed a large variety of animal densities in Italy, ranging from zero to up to more than ten, depending on the characteristics of the territory and its vegetation stratum [26].…”
Section: Introductionmentioning
confidence: 97%